2019
DOI: 10.5812/jjcdc.84819
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mindfulness-Based Stress Reduction Group Therapy in Rumination Among Multiple Sclerosis Patients

Abstract: Background: Multiple sclerosis (MS) is a disabling neurological disorder, which in addition to neuro-motor disorders, accompanies a variety of symptoms, such as anxiety, asthenia, and reduced levels of problem-solving, and leads to a number of physical and mental disorders. This is while rumination is among psychological problems that can negatively affect MS patients' mental health. Rumination is known as a permanent engagement in a thought or an issue and is categorized as a conscious thought focused on a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…The between-group study indicated that there is a signi cant difference between the mean scores of rumination in both groups which means that immediately and one month after the intervention, the mean score of rumination in the control group was more than that of intervention group; although in within-groups comparison, the decrease caused in the intervention group was not signi cant, the between-group difference resulting from this decrease in the intervention group and an increase in mean score in control group show that patients in the intervention group are better than the control group in terms of rumination. The results of the present study are consistent with those of some studies ( Campbell et (16,17,23,31,35,36). These studies aimed to demonstrate the effectiveness of mindfulness and the results indicated the positive effect of mindfulness on decreasing rumination in patients with breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…The between-group study indicated that there is a signi cant difference between the mean scores of rumination in both groups which means that immediately and one month after the intervention, the mean score of rumination in the control group was more than that of intervention group; although in within-groups comparison, the decrease caused in the intervention group was not signi cant, the between-group difference resulting from this decrease in the intervention group and an increase in mean score in control group show that patients in the intervention group are better than the control group in terms of rumination. The results of the present study are consistent with those of some studies ( Campbell et (16,17,23,31,35,36). These studies aimed to demonstrate the effectiveness of mindfulness and the results indicated the positive effect of mindfulness on decreasing rumination in patients with breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Since the ability to think about what is not happening is a cognitive achievement that comes at an emotional cost 7 , learning how to monitor and accept present moment experience, as in mindfulness interventions, could help to enhance attentional control and thus reduce MW and emotion dysregulation 38 . Accordingly, consistent evidence indicates that mindfulness based therapy could help PwMS by focusing on the present instead of the future and by increasing self-monitoring and awareness of their own body, which may lead to a significant reduction in psychological symptoms, including anxiety and depression, and improved self-care 5,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the negative content of MW, known as rumination that is referred to as persistent and recurring thoughts associated with a common issue, can increase the likelihood and the intensity of depression and excessive rumination predisposes to the increased risk of depression 11 . Indeed, many people believe that when they become sick, they have to try to focus on their inner strengths because they think that such a concentration will give them the insight to find a solution to their problem 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness is a third-wave therapy that has received considerable attention in recent years. Through the mindfulness practices, participants learn to observe their thoughts and feelings (21). Mindfulness skills training increases individuals' motivation to achieve and stay committed to their goals, reduce avoidance, and believe in the chance and perceived duration of the goal (22).…”
Section: Introductionmentioning
confidence: 99%